The Effect Of Leverage And Profitability On Investment Decisions: A Study On Property Companies Listed On The IDX - Karona Cahya Susena (UNIVED Press, 2024)
This study aims to determine the analysis of the influence of profitability, leverage on investment decisions in the hotel, restaurant and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX) with research observations in 2020-2021. The method in selecting the sample is using non-probability sampling with purposive sampling and the selected sample is 17 issuers. Data collection techniques in this study used secondary data, namely library research and documentation. For data analysis techniques using multiple linear regression data analysis techniques. Based on the result of the study that the leverage variable has an effect on investment decision. Meanwhile, profitability and liquidity have no effect on investment decision.